Incidence, Management Practices, and Training Needs for Gingival Accidents Among Dental Professionals: A Survey-Based Study - Karima Alfitory Ahmed; Rasha Ibrahim; Ghada Gehani (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Gingival accidents, including chemical burns and mechanical trauma, are prevalent incidents in dental practice that can significantly impact patient care. Despite the common occurrence of these accidents, there is a notable gap in training among dental professionals regarding their management. This study aimed to assess the incidence of gingival accidents, the management practices employed, and the training needs of dental practitioners. Materials and Methods: A total of 313 dental professionals from Libya, including general dentists, dental hygienists, and dental specialists, participated in a survey designed to collect demographic information, the incidence of gingival accidents, management strategies employed, and awareness of protective measures. Statistical analyses were performed to determine the relationships between demographic factors and reported practices. Results: The study found that 70% of respondents encountered gingival accidents in their clinical practice. Chemical burns constituted 55% of reported incidents, while 35% were attributed to mechanical trauma. Immediate management strategies included washing the affected area with water (60%) and applying Vitamin E (30%). However, only 35% of respondents reported receiving formal training in managing gingival accidents, and 85% of those without training expressed a desire for further education. Additionally, only 45% of practitioners routinely employed protective measures.